KEPEMIMPINAN DALAM PEMBAHARUAN SEKOLAH - Erma Niarti (Manajer Pendididikan, 2016)
The formulation is a common problem in the management of school leadership renewal in Junior High School 3 Ketahun North Bengkulu district. This research is a qualitative descriptivestudy design. The results of this study show: First, the leadership of principal in implementing reforms in the academic field are optimal with strong involvement of the principal as a supervisor. Second, the leadership of principal in implementing reforms in the field of school administration well, with strong involvement of the principal as an administrator. Third, the leadership of principal in implementing reforms in the financial sector is quite successful, with good financial management schools include: financial planning, financial resources, financial management and accountability.Keywords: leadership, principals, management reform